Community-based Ecotourism in Tenganan Dauh Tukad: An Indigenous Conservation Perspective - I Ketut Sardiana; Ni Luh Ramaswati Purnawan (Universitas Udayana, 2015)
Community-based ecotourism involves conservation, business, and community development. It is a subset of nature-based tourism that are owned and managed by the community and used to improve the well-being of its community members. Research conducted in Indigenous Tenganan Dauh Tukad Village, Bali. This paper examines the linkage of community participation in ecotourism with the conservation practices and perspectives. This study revealed that there is a positive linkage between community participation to their practices and perspective of conservation. This includes conservation of biodiversity environment and cultural heritage of the local community.